INFLUENCE OF PROFITABILITY, LEVERAGE AND SIZE OF COMPANY ON INCOME MANAGEMENT (Case Study of Pharmaceutical Sub Sector Manufacturing Companies Listed on the Indonesia Stock Exchange 2015 – 2018) - Titik Hasriani; Helmiati Helmiati; Rahmawati Rahmawati (STIE Bangkinang Publishing, 2021)
This research was conducted with the aim of examining the effect of profitability, leverage and company size on earnings management in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. The population in this study were all pharmaceutical sub-manufacturing companies listed on the Indonesia Stock Exchange. 2015-2018, namely 12 companies. The technique used in sampling is purposive sampling method, the sample in this study was selected as many as 9 companies. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 22.00 for windows. The results showed that simultaneously profitability, leverage and firm size have an effect on earnings management. Partially, the company size has an influence on earnings management.